Antibodies to lassa virus Z protein and nucleoprtein co-occur in human sera from lassa fever endemic regions (2001)
It is not known whether the small 11-kDa Z protein of lassa virus is immunogenic during human lassa virus infection. To obtain evidence for the existence of an antibody response and to test the suitability of these antibodies for serosurveys, sera from lassa fever endemic regions(Guinea and Nigeria, n=75) were tested for co-reactivity to Z protein and nuclcoprotein (NP). Sera from a non-epidemic region (Uganda, n=50) served as a specificty control. Z protien and NP were expressed in Escherichia coli, affinity-purified, and used as antigen in western blot. Indiredt immunofluorescence (IIF) with lassa virus-infested cells was performed for comparison. Due to high unspecific reactivity of the African sera, western blot testing was performed with a 1:1,000 serum dilution. Under these conditions, none of the control sera but 12% of the sera from endemic regions co-reacted with both Z protein and NP. REactivity to Z protien was significantly associated with NP reactivity (p<10-6). Np and Z protein- specific antibodies were co-detected in 33% of the IIF-positive sera and in 5% of the IIF-negative sera (P=0.001). These data provides evidence for apperance of antibodies to Z protien and NP following Lassa virus infection. A recombination blot for detection of both antibody specificities seems to be specific but less sensitive than IIF.